Relationship between family dynamics, spirituality, quality of life and happiness among older adults in Nigeria (2023)
Happiness of older adults in rarely studied in the global south like Nigeria compared with the global north. This study assessed the relationship between family dynamics, spirituality, quality of life and happiness among older adults in Nigeria. Cross-sectional study of 378 older adults (≥60 years) were selected. Oxford Happiness questionnaire, the family dynamics, spirituality, and quality of life (QoL) were determined with the Family Relationship Index, spiritual Index of Well-being scale and Quality-of-Life Brief questionnaire respectively. Descriptive and inferential statistics were carried out at α0,05. The mean age was 72,8±7,1 years and 255 (67,5%) were females. Majority 313 (82,8%) were assessed to be happy. Overall, family dynamics, spirituality, and health related QoL were significantly determinants of happiness (p<0,05). Among the women, there was good cohesion in the family dynamics (p=0,031), good health related QoL in the physical domain (p<0,001) and satisfaction with health (p=0,036) were the predictors of happiness. Having higher self-efficacy (p=0,018) and life scheme spirituality (p=0,050) were the predictors of happiness among the men. The present findings showed that most of the older adults were happy. Routine assessment and interventions could increase the feeling of happiness among older adults in the global south.